THE ROLE OF COMMUNITY LEADERS IN BUILDING TOLERANCE AMONG RELIGIONS - Fransiska Dian Andanasari; Hj. Yuliatin; H. Dahlan (Journal Civics And Social Studies, 2021)
This research aims to find out the role of community leaders in fostering tolerance between religious communities in Karang Baru Village, Mataram City, as well as finding out other things related to tolerance in society. The type of research used in this research uses qualitative methods, a descriptive approach and a phenomenological theoretical basis. Data collection techniques use interviews, observation and documentation. Data analysis techniques by means of data collection, data reduction, data presentation, conclusions and verification. The technique for testing the validity of data uses triangulation (combination). Thus, researchers can see how community figures foster tolerance between existing religious communities through the roles that community figures carry out in accordance with their position.